(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2021)
Common bacterial blight, caused by Xanthomonas axonopodis pv. phaseoli, is an economically important disease of common bean and causes significant yield losses in Ethiopia. A field survey was conducted to understand the spatial distribution, relative importance and association of common bacterial blight epidemics with agro-ecological factors in low and mid-land areas of Southwestern, Ethiopia, during the 2018-19 cropping season. A total 85 bean fields were assessed in four common bean growing districts. High diseases incidence and severity was recorded at Debub Ari (77.6 and 52.7%, respectively) while the lowest was from Male (38.5 and 28.0%, respectively). The associations between disease parameters and agro-ecological factors were analyzed using multiple logistic regression models. Agronomic practices including NPS fertilization, preceding crop, weed management and plant population had highly significant (P<0.0001) association with both disease incidence and severity. Also, altitude, seed source and cropping system significantly (P<0.05) influenced disease severity while cropping pattern showed significant (P<0.05) association with disease incidence in the reduced model. Higher mean disease severity (≥40%) had high probability of association with district, absence of NPS fertilization, poor weed management practice, and preceding crops, than their counter parts. Adequate NPS fertilization increases growth performance of the crop in turn decreases disease intensity, weed serve as alternate host for incoming inoculum and previous crops were source for inocula as well as crop rotation used as reduce inoculum load. Therefore, the present study showed that the disease is a major production constraint of common bean, and suggested proper nutrient and weed management practices, and crop rotation to reduce common bacterial blight in the study areas. Int. J. Agril. Res. Innov. Tech. 11(1): 74-83, June 2021